Religions in Times of Peace: Conceptualizing the Practice of Interreligious Dialogue in the Post‐ Conflict Environment - Lailatul Fitriyah (Indonesian Perspective, 2016)
The article makes the case of collaborating the notion of interreligious dialogueand the concept of the zone of peace in an attempt to provide a more practical yeteffective channel of reconciliation in the context of post‐interreligious violence. There arethree critics implied throughout the article. First, that the current state of most ofinterreligious dialogue in post‐conflict settings is lack of two things, namely, the inclusivestructure that would allow non‐scholars and non‐clergies to engage in the theologicaldialogue, and a coherent structure for the currently diasporic efforts in interreligiousdialogue. Second, that the concept of zone of peace is severely limited, particularly due toits dependence on material modalities in forging the path of reconciliation toward peace.And third, that the elusive and elitist nature of interreligious dialogue in post‐conflictsettings, and the limited material modalities of the zone of peace can be expanded bycollaborating the two notions into an applicable zone of interreligious peace. Lastly, thepaper will take the case of the village of Latta in Maluku to present a practical context forthe zone of interreligious peace.Keywords: interreligious dialogue, zone of peace, post-interreligious violence